Discursive Freedom in Alexandre Najjar’s Political Writings - Ikram Aya Bentounsi , Lilia Harkou (Migration Letters, 2024)
This article examines the use of axiological adjectives, verbs, and adverbs in Alexandre Najjar’s Lebanese political discourse. It shows that through his vision, criticisms, and attitudes toward socio-political events, the speaker crosses borders, gets closer to his reader, and expresses his views frankly and freely.